Kajian Nilai-Nilai Dasar Kehidupan pada Sastra Lisan Ternate - Masayu Gay (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
This is a descriptive analytical research which aims to reveal the basic values of life in Ternate oral tradition (dola bololo, drums proposition, and Moro proposition). The values are assessed through structural and hermeneutic approach. The results indicate that dolabololo reflects fundamental values of (1) generosity; (2) prohibition against hurting others; (3) The man and his world; (4) pluralism. Dalil tifa reflects Islamism, togetherness, affection, humanity and death.